A Retrospective Analysis of Visit Durations and Referral Attendance for Pediatric Ocular Conditions Seen in Emergency and Urgent Care Settings - Madelin Z. Ching BS; Kelly Romesburg BS; Catherine O. Jordan MD; David L. Rogers MD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Outpatient clinic access for patients diagnosed with non-emergent ocular conditions has been shown to decrease patient load in the Emergency Department (ED)/Urgent Care and improve patient satisfaction with care. We sought to quantify referral completion rates and ED/Urgent Care visit durations at a pediatric tertiary care center and analyze how demographic factors may influence these quality indicators. We discuss an overarching strategy to improve access to subspecialty care through a same-day access program. We retrospectively reviewed ED/Urgent Care patient encounters from 2019 to 2024. Patients diagnosed with conjunctivitis, vision loss, corneal abrasion, or iritis referred for follow-up care were included in this report. Visit duration in the ED/Urgent Care, referral completion rates, and patient demographics were analyzed. Seven hundred six patient encounters met the initial inclusion criteria. The average visit duration in the ED/Urgent Care per month was 3.36 hours (median, 3.45; IQR, 2.84-3.81), the average proportion of incomplete referrals per month was 21.9% (median, 20%; IQR, 10.6%-30%), and average proportion of ED/Urgent Care visits over 4 hours per month was 33.1% (median, 33.3%; IQR, 21.3%-43.5%). Demographic subgroup analysis (n = 411) revealed a relationship between age, insurance status, zip code, and race with completed referral rates and visit duration in the ED/Urgent Care. Our results indicate long visit durations in the ED/Urgent Care and a large proportion of incomplete referrals for patients with non-emergent ocular issues. A same-day access program could streamline access to subspecialty care by moving patients directly to the ophthalmology department from the ED/Urgent Care.